Regional Legislative Entrepreneurship in Indonesia: Actors, Strategies, and Institutional Constraints - Wawan Sobari (ARISTO, 2027)
This study examines regional legislative entrepreneurship (LE) in Indonesia, focusing on the Regional Legislative Council (DPRD). It investigates the origin of a regional bill (raperda) on Cultural Advancement initiated by the DPRD of the Malang Municipality. This study adopts a political entrepreneurship analytical framework and explores four categories: who, how, where, and impact. Utilizing qualitative methods and interviews for data gathering, the findings indicate that legislators are instrumental in formulating regional regulations, while political parties influence the content of the draft. The approach to legislation is normative and adheres to the government directives. Legislators support the drafting of regional regulations based on logical reasoning, national law requirements and party directives. Thus, this study contributes theoretical insights affirming the crucial interplay between institutions and rational political behavior in fostering LE, as identified in previous studies. Nevertheless, this interplay is not concurrent; government bodies regulate the enactment of regional laws through oversight, thereby limiting LE practices at the regional tier. However, as this study is based on a single municipal case and focuses on one policy sector, future research should compare DPRD-initiated bills across regions and policy domains to test the broader applicability of regional legislative entrepreneurship in Indonesia.